1325Zero-fluoroscopy cryoablation for treatment of atrioventricular nodal reentry tachycardia in adult and pediatric patients. (18th June 2020) - Prolic Kalinsek, T; Zizek, D; Stublar, J; Kuhelj, D; Jan, M
Abstract: Funding Acknowledgements: None Introduction Cryoablation is considered a safe but somewhat less effective alternative to radiofrequency ablation (RF) for treatment of atrioventricular nodal reentry tachycardia (AVNRT). Additionally, it is traditionally performed with the aid of X-ray fluoroscopy as the principal imaging method causing radiation exposure, which is especially undesired in the pediatric population. Purpose: The aim of our study was to assess feasibility, safety and success rate of nonfluoroscopic cryoablation for treatment of AVNRT. Methods: Forty-eight consecutive patients with a diagnosed AVNRT (aged 40 ± 22 years, 29 (60%) female, 19 (40%) male) were included in the study. Among the study population, 14 (29%) were pediatric patients aged 11.5 ± 4.1 years. Cryoablation was used at the discretion of the operator. Only three dimensional electroanatomic mapping system and intracardiac electrograms were used to guide catheter movement and positioning. X-ray fluoroscopy was not used. The initial approach in all procedures was cryomapping in the region of the slow pathway during ongoing AVNRT, with a switch to cryoablation when termination of tachycardia within 20 seconds of reaching -30°C was achieved. When cryomapping was not possible due to catheter instability, cryoablation was used during ongoing AVNRT for up to 10 seconds at -70°C or lower. When AVNRT was not readily inducible, termination of slow pathway conduction was targeted with cryomapping during programmed stimulation with atrial extrastimuli. Procedural endpoint was noninducibility of AVNRT. Recorded residual slow pathway conduction was not considered a failure. Results: Mean procedural duration was 79 ± 34 minutes. On average, 4 ± 2 cryoablations, with a 240 seconds of cryoablation time per each application. Cryoablation was used as a first choice in 45 (45/48, 93.7%) patients. In the remaining 3 patients (3/48, 6.3%) RF ablation failed as the first choice due to transient AV conduction disturbance and cryoablation had to be used to reach the endpoint. Cryoablation was unsuccessful only in 3 cases (6.6%) where RF ablation was needed to achieve procedural endpoint. Targeting termination of AVNRT during cryomapping or cryoablation was possible in 25 patients (25/48, 52%). In 14 patients AVNRT was not inducible and termination of the slow pathway conduction was targeted instead. In 9 patients inadvertent catheter tip contact mechanically terminated AVNRT or slow pathway conduction; site of mechanical termination was then targeted with cryoablation. After mean follow-up of 349 ± 201 days 47 patients were free of recurrence (47/48, 98%). There were no procedural complications. Conclusions: In our study population with adult and pediatric patients, zero-fluoroscopy cryoablation of AVNRT proved feasible, safe and resulted in high success rates. Cryomapping or cryoablation for AVNRT termination was possible in approximately half of the procedures.